Pengaruh Model Pembelajaran Probing Promting Terhadap Kemampuan Metakognitif Siswa (Studi Quasi Eksperimen Siswa Fase B Kelas IV Mata Pelajaran IPAS di SDN 1 Cigadung) - Amanda, Hemalia; Simbolon, Marlina Eliyanti; Hermawati, Eli (Metodik Didaktik, 2024)
The research was motivated by students who have not been able to answer when faced with problems, hesitate to solve problems in learning, and have not been able to evaluate learning. The study aims to determine the difference and increase (gain) of students' metacognitive abilities in experimental and control classes. The research used a quasi-experimental method with a nonequivalent control group design. The research subjects were students of class IV A and IV B of SDN 1 Cigadung, Cigugur District, Kuningan Regency. The variables of this study were probing prompting learning model and students' metacognitive ability. The results of the posttest data analysis calculation show the tcount value of 3.502 and the ttable value of 5.991 (tcount ttable). Based on the criteria for submitting a hypothesis, H1 is accepted. This shows that there is a difference in posttest between the experimental class and the control class. The results of the gain test in the experimental class are in the medium category, while for the control class in the low category. So this shows that there is a difference in the improvement (gain) of students' metacognitive abilities in the experimental class and the control class. The application of the probing prompting learning model in the learning activities of grade IV IPAS subjects at SD Negeri 1 Cigadung in the even semester of 2023/2024 was successfully implemented. It can be concluded that the application of the probing prompting learning model affects the metacognitive abilities of IPAS subjects.Penelitian dilatarbelakangi siswa yang belum mampu menjawab ketika dihadapkan pada soal, ragu untuk mengatasi masalah dalam pembelajaran, dan belum mampu mengevaluasi pembelajaran. Penelitian bertujuan untuk mengetahui perbedaan dan peningkatan (gain) kemampuan metakognitif siswa pada kelas eksperimen dan kelas kontrol. Penelitian menggunakan metode adalah quasi eksperimen dengan desain nonequivalent control group design. Subjek penelitian adalah siswa kelas IV A dan IV B SDN 1 Cigadung Kecamatan Cigugur Kabupaten Kuningan. Variabel penelitian ini adalah model pembelajaran probing promting dan kemampuan metakognitif siswa. Teknik pengumpulan data dalam penelitian adalah tes uraian. Hasil perhitungan analisis data posttest menunjukkan nilai thitung 3,502 dan nilai ttabel 5,991(thitung ttabel). Berdasarkan kriteria pengajuan hipotesis maka H1 diterima. Hal ini menunjukkan terdapat perbedaan posttest antara kelas eskperimen dan kelas kontrol. Hasil uji gain pada kelas eksperimen masuk dalam kategori sedang, sedangkan untuk kelas kontrol masuk kategori rendah. Sehingga hal ini menunjukkan terdapat perbedaan peningkatan (gain) kemampuan metakognitif siswa pada kelas eksperimen dengan kelas kontrol. Penerapan model pembelajaran probing promting pada kegiatan pembelajaran mata pelajaran IPAS kelas IV di SD Negeri 1 Cigadung pada semester genap 2023/2024 berhasil dilaksanakan dengan baik. Dapat disimpulkan bahwa penerapan model pembelajaran probing promting berpengaruh pada kemampuan metakognitif mata pelajaran IPAS.